(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2024)
Lepironia articulata or the kolosua is a species of herbaceous plant from the Cyperaceae family used as a raw material for weaving crafts. The woven craft of kolosua is one of the additional incomes of the local community on Wawonii Island. This study aims to find out local knowledge about the utilization of kolosua as handicraft, various handicraft products, and the problems faced by craftsmen so that the plant species can be considered for local government policies in terms of using kolosua to increase people’s income and environmental regulations to maintain their natural habitat. An ethnobotanical study on the utilization of kolosua by the local community in Wawonii Island was carried out by semi-structured and "open-ended" interviews, and direct observations in the field. Lepironia articulata is one species of plant that is used as raw material for woven crafts. Generally, handicraft products are produced for craftsmen’s use or sold to traditional markets on Wawonii Island. Art and craft products are one of the sources of community income. The income from the sale of kolosua woven products was around IDR 100,000 (USD 7) up to IDR 150,000 (USD 10) after deducting transportation costs. The role of local governments is needed to provide awareness counseling on the use of kolosua. This study has implications for the local community and government to increase people’s income, environmental regulations and to maintain their natural habitat.